A ANALISIS STRUKTUR DAN EFISIENSI BIAYA PROGRAM PENGELOLAAN SAMPAH BERABSIS MASYARAKAT DIPERKOTAAN STUDI KASUS BANK SAMPAH UNIT SEROJA KELURAHAN PANDANG PANDANG KABUPATEN GOWA: ANALISIS STRUKTUR DAN EFISIENSI BIAYA PROGRAM PENGELOLAAN SAMPAH BERABSIS MASYARAKAT DIPERKOTAAN - Arnida, Arnida; Meda, Tamrin; Sabrida, Sabrida (Lembaga Penelitian, Publikasi dan Pengabdian Pada Masyarakat, 2025)
This study aimed to analyze the impact of organizational structure and cost efficiency on the performance of a community-based waste management program at BSU Seroja Gowa. This quantitative research employed a survey method with a population of 50 respondents directly involved in the program. Data were collected using questionnaires and analyzed with multiple linear regression. The results of the partial t-test indicated that organizational structure had a positive and significant effect on program performance (p<0.05). Similarly, cost efficiency was also found to have a positive and significant effect on program performance (p<0.05). Simultaneously, the F-test results confirmed that organizational structure and cost efficiency together had a significant impact on program performance. The coefficient of determination (R2) was 0.685, indicating that 68.5% of the variation in program performance can be explained by these two variables, while the remaining 31.5% is influenced by other factors outside the model. These findings underscore that the design of an effective organizational structure and efficient cost management are crucial factors for the success of community-based waste management programs. The practical implications of this research are recommendations for the management of BSU Seroja Gowa to focus efforts on strengthening these two aspects to optimally enhance program performance.